1998
DOI: 10.1159/000054334
|View full text |Cite
|
Sign up to set email alerts
|

Is GnRH Reduced at the Midcycle Surge in the Human?

Abstract: Recent studies indicate that the midcycle gonadotropin surge in the human occurs without an increase in hypothalamic gonadotropin-releasing hormone (GnRH) pulse frequency. In addition, previous studies employing a GnRH antagonist to provide a semiquantitative estimate of endogenous GnRH secretion suggest that the overall amount of GnRH secreted is decreased at the time of the surge. To investigate the hypothesis that a normal gonadotropin surge can be generated in the human with a decreased amount of GnRH at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
1
9
0
1
Order By: Relevance
“…3, 6, and 39), a diminished diurnal rhythm of suprachiasmatic nucleus input (17), and reduced responsiveness to kisspeptin (18). However, there is considerable evidence that estrogen positive feedback in women is mediated primarily at the pituitary, with hypothalamic GnRH secretion playing only a permissive role (14,15,21). Neuroanatomic studies in PMW undergoing a graded steroid infusion similar to that used in the current studies indicate that negative feedback is associated with a decrease in metabolic activity in the medial basal hypothalamus followed by increased pituitary, but not hypothalamic, activity associated with positive feedback (22), suggesting that in PMW, as in reproductive-aged women, the positive feedback effect resides primarily at the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…3, 6, and 39), a diminished diurnal rhythm of suprachiasmatic nucleus input (17), and reduced responsiveness to kisspeptin (18). However, there is considerable evidence that estrogen positive feedback in women is mediated primarily at the pituitary, with hypothalamic GnRH secretion playing only a permissive role (14,15,21). Neuroanatomic studies in PMW undergoing a graded steroid infusion similar to that used in the current studies indicate that negative feedback is associated with a decrease in metabolic activity in the medial basal hypothalamus followed by increased pituitary, but not hypothalamic, activity associated with positive feedback (22), suggesting that in PMW, as in reproductive-aged women, the positive feedback effect resides primarily at the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…8.8). 108 Taken together, these studies indicate that GnRH is absolutely required for generation of the midcycle surge in normal women; however, there is no evidence for an increase in either the amplitude or frequency of GnRH secretion. 107 Results of these studies provided no evidence for an increase in the overall amount of GnRH secreted and, in fact, suggested that the amount of GnRH at the surge is less than in the early and late follicular phase.…”
Section: Midcycle Surgementioning
confidence: 81%
“…101 In the rat and sheep there is evidence that in addition to pituitary augmentation of the GnRH signal, estrogen positive feedback on gonadotropin secretion requires an increase in GnRH secretion 102 and in rodents, this increase in GnRH secretion requires specific circadian signals. [106][107][108] Taken together, these data suggest that the gonadotropin surge in normal women requires ongoing pulsatile GnRH stimulation, but is otherwise mediated through the marked increase in pituitary sensitivity to GnRH (discussed later in the chapter in Midcycle Surge). While kisspeptin appears to be involved in both negative and positive estrogen feedback in the rodent, kisspeptin neurons in the arcuate nucleus coexpress NKB and dynorphin, whereas this is not the case in the AVPV.…”
Section: Estrogenmentioning
confidence: 82%
“…168 Similarly, pulsatile administration of constantdose exogenous GnRH produces LH surges in GnRHdeficient women 162 ; indeed, LH surges can occur in such women even when pulsatile GnRH doses are reduced at midcycle. 169 Also, while pituitary metabolic activity (by positron emission tomography) increases in women at midcycle, hypothalamic metabolic activity does not. 170 Thus, although continued GnRH stimulation plays a critically important permissive role in LH surge generation in women (e.g., the surge can be prevented with GnRH receptor antagonists 171,172 ), available data do not suggest that the gonadotropin surge is accompanied by increased GnRH release in women.…”
Section: Positive Feedback and The Mid-cycle Gonadotropin Surgementioning
confidence: 99%